TINJAUAN KONDISI FISIK MEMBER FITNES G-SPORT CENTER KOTA PADANG - Gemi Gemi; Anton Komaini; Arif Fadhli Muchlis (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
The problem in this research is condition of the physical condition of the G-Sport Center Members of the City of Padang does not yet know which includes Aerobic Endurance, Strength, Speed, and Flexibility. This study aims to determine the physical condition of Members of the Padang City G-Sport Center Fitness with regard to Aerobic Endurance, Strength, Speed, and Flexibility. The population of this research is members who actively take training in G-Sport Fitnes, Padang City totaling 129 people. The sampling technique is done by Proportionate Stratified Random Sampling, the sample in this study were 21 people. Data collection is done by measuring the physical condition of Padang City G-Sport Center Members, including Aerobic Endurance with Harvard test, strength test with push strength test, Speed ​​test through 50 Meter Running test, agility test with Sit and Reach test. The data analysis technique uses descriptive statistics (frequency tabulation). The results of the study can be obtained: